Brazilian sign language as a tool to promote oral health for hearing-impaired patients: A Dentistry primer in Libras (Research, Society and Development, 2022)
Hearing loss is a type of sensory deprivation, regarded as an abnormal reaction to sound stimuli. Deafness is, therefore, characterized by a greater or lesser degree of loss of normal perception of sounds. Aiming at the integrality of care for people with hearing loss and so that health promotion is achieved, it is necessary that family members, caregivers, patients, and professionals have access to material and quality guidance on oral health care. To help students, teachers and dental professionals to provide a more accessible and humanized service to this public, a booklet was prepared with oral hygiene instructions in Brazilian Sign Language, to provide guidance on health promotion aspects. It contains the first contact, through signs, to communicate with the patient and oral hygiene instructions that help improve the service and the relationship between professional and patient.